A INFLUÊNCIA DA VOLUMETRIA ARQUITETÔNICA NO DESIGN DE MOBILIÁRIO CONTEMPORÂNEO (ESTUDO DE CASO: O TRABALHO DE AUGUSTO THOMÉ). - RORIZ JÚNIOR, Laudemiro (2008)
The present work consists of the result of a research, whose objective age to identify the historical and stylistic influences that act in the furniture of designer Augusto Thomé, who got his architectural formation and acts professionally in Goiânia. The region of the city and its outskirts are furniture polar region of national representation. The study of the history of the city, in its foundation and marked moment of its growth, which happened with the construction of Brasília, it was necessary for the agreement of the lines traced in design of Thomé. In Goiânia, characteristics of art déco in the urbanistic plant, in monuments and historical buildings, dated of its foundation, and the modernist monumentalism of Brasília, they determine the formal references of the associations between volumes, plans and lines that generate the identity of the creation of Thomé. The architectural and furniture conceptions of these moments, analyzed in a world-wide context of influence on our culture, are gifts here, as parts of the formation of our social values and aspirations of development.